KEUNTUNGAN RELATIF BENTUK OLAHAN MINYAK KELAPA DI KECAMATAN AMARASI - Johny Agustinus Koylal (Partner, 2008)
Relative Profits of the Product of processed form of coconut oil in Amarasi district. This research aims at knowing the amount of relative profits of processed form of coconut oil in Amarasi district. This research was held since March 2007 until October 2007 in Amarasi district of Kupang regency of East Nusa Tenggara. This employs descriptive method and its data-collecting technique employs survey one. Tesbatan and Apren villages were chosen as samples area by purposing-sampling method. Technique to choose farmers as the respondents is done by using census way and it gets 48 farmers. Data were analyzed by using input-output way in order to know the amount of profits of a processed form, that is, coconut oil. If you are keen on gambling, you are likely to enjoy playing games at an online casino. And an online casino real money no deposit Australia can offer will certainly give you a lot of thrill. You will get a real casino experience, hours of fun, and burst of emotions. There you can get other bonuses as well as soon as you decide to make a deposit. To know relative profit of processed form of coconut oil, it uses R/C ratio (return and cost).Result show that according to calculation result of R/C ratio, it finds that relative profits on cash fee of coconut oil production are about 2.98 (strata I); 2.83 (strata II); and 3.45 (strata III).Keywords: relative, profits, coconut, and oil